KDM5C Represses FASN-Mediated Lipid Metabolism to Exert Tumor Suppressor Activity in Intrahepatic Cholangiocarcinoma - Zhang, Bo; Zhou, Bing-hai; Xiao, Min; Li, Hui; Guo, Lei; Wang, Meng-xi; Yu, Shan-he; Ye, Qing-hai (Frontiers in Oncology, 2020)
Background: KDM5C is a histone H3K4-specific demethylase, which has multiple biological functions during development and disease. However, the role of KDM5C in cholangiocarcinoma (ICC) remains unknown. Methods: Expression levels of KDM5C in ICC patients were determined by qRT-PCR, western blotting and immunohistochemical assay. The functions of KDM5C in cell proliferation and invasion were determined in human ICC cells and mouse xenograft model using KDM5C overexpression and knockdown strategies in vivo. RNA-seq analysis was applied to investigate the transcriptional program of KDM5C. In addition, ChIP-qPCR was used to determine the regulation of FASN by KDM5C. Results: Here, we show that KDM5C was downregulated in human ICC, where its diminished expression was associated with poor prognosis. ICC cell proliferation and invasion were inhibited by KDM5C overexpression. Moreover, KDM5C suppressed ICC proliferation and metastasis in vivo. RNA-sequencing showed that KDM5C inhibits key signal pathways of cell proliferation, cell invasion and fatty acid metabolism. ChIP-qPCR revealed that overexpression of KDM5C led to the reduction of H3K4me3 on the promoter and the corresponding downregulation of the expression of FASN, which represents the major target gene of KDM5C to mediate the proliferation and invasion of ICC cells. Conclusions: Our results revealed the role of KDM5C as a novel tumor suppressor in ICC largely by repressing FASN-mediated lipid acid metabolism and thus KDM5C may contribute to the pathogenesis of ICC.